New insights on Raman spectrum of K‐bearing tourmaline. (9th September 2019) - Musiyachenko, K.A.; Korsakov, A.V.; Shimizu, R.; Zelenovskiy, P.S.; Shur, V. Ya
Abstract: Raman spectroscopy allows for semiquantitative analyses of major elements of tourmaline supergroup minerals. However, the new K‐bearing tourmaline (maruyamaite) species has not been calibrated yet and the effects of K in the X site of tourmaline on the Raman spectrum are still unclear. We investigated maruyamaite and K‐bearing dravite to test their Raman spectrum parameters, as a proxy for chemical composition of the X site. This study uses Raman imaging to obtain spectral data from the studied area of the zoned natural tourmaline crystals from Kumdy‐Kol (Kokchetav massif, Northern Kazakhstan). These data are correlated with chemical composition determined by electron probe microanalysis. Raman peak intensity best correlates with the K apfu at the X site. Peaks in the interval 100–250 cm −1 are aligned to the X‐site cation vibrations, and thus, their intensity positively correlates with K content. However, also, the more intensive peaks in the 650 to 850 cm −1 interval, which are controlled by the Si6 O18 ring and AlO6 vibrations, show a positive correlation with the amount of K. The latter peak region is thus chosen here for the calibration due to its much higher intensity respect to the 100 to 250 cm −1 region. Furthermore, we discuss the influence of large K cations on the structure of Si6 O18 rings in tourmaline. Our study demonstrates that Raman spectroscopy can be used as a reconnaissance tool for a semiquantitative discrimination of dravitic tourmalines with different X‐site occupation. Abstract : We established correlations between K content in tourmaline and intensity of the Raman peaks in the 650–850 cm −1 range. Large K cations influence the peak intensities in the 650–850 cm −1 interval, which are controlled by the Si6 O18 ring and AlO6 vibrations. Raman spectroscopy can be used as a reconnaissance tool for a semi‐quantitative discrimination of dravitic tourmalines with different X‐site occupation.